The Effect of Digital Communication and Technology-Based Training on Employee Performance Through Work Culture at PT JPS - Wulansari, Nadya; Uus Mohammad Darul Fadli,; Ery Rosmawati, (Research in Management of Technology and Business, 2026)
Digital transformation has driven changes in work systems across industries, including the steel and construction sector; however, empirical studies examining the role of digital communication and technology-based training in this sector remain limited, particularly in relation to employee performance through work culture. This study aims to analyze the effect of digital communication and technology-based training on employee performance through work culture at PT JPS. A quantitative approach was employed using a survey of 81 respondents selected through simple random sampling and analyzed using SEM-PLS with SmartPLS. The results show that digital communication has a significant positive effect on work culture and employee performance, while technology-based training has a significant positive effect on both variables with a stronger contribution. The model explains 73.7% of the variance in work culture and 85.9% of the variance in employee performance. However, work culture does not have a significant effect on employee performance and does not mediate the relationship between digital communication and employee performance or between technology-based training and employee performance. These findings indicate that employee performance is more directly influenced by communication quality and training effectiveness than by work culture, highlighting the importance of strengthening digital communication and technology-based training in organizational practices.